Removal of proximally migrated biliary stents by using single-operator cholangioscopy - Abed Al Lehibi, MD; Abdullah Al Mtawa, MD; Thamer Almasoudi, MD; Adel Al Ghamdi, MD; Nawwaf Al Otaibi, MD; Areej Al Balkhi, MD (VideoGIE, 2020)
Background and Aims: Migration is a late adverse event of biliary stent placement. It occurs in 1% to 20% of cases and is associated with a diverse array of adverse events. In this article, we report our take on endoscopic extraction of proximally migrated biliary stents by the use of single-operator cholangioscopy. Methods: This report includes 3 patients who were found to have proximal stent migration while being treated for biliary stones. One patient had a migrated metal stent, and the other 2 had plastic stents. Single-operator cholangioscopy was used to retrieve the stents in all patients. The SpyBite biopsy forceps accessory was used to extract the metal stent, whereas the SpyBasket and the SpySnare were used to extract the plastic stents. Results: All patients underwent successful stent removal by the techniques described in this report, with no immediate adverse events, and they completed more than 4 weeks of follow-up care with no further adverse events. Conclusions: Digital single-operator cholangioscopy with SpyBasket, retrieval snare, and SpyBite biopsy forceps can be useful tools to remove migrated plastic and metallic stents, respectively.